Kinerja Keuangan Perusahaan Transportasi Pra dan Masa Pandemi Covid-19 - Sari, Anisa Kantata; Hardiyanti, Widhian (Jurnal Informatika Ekonomi Bisnis, 2023)
The rapid spread of the Covid-19 outbreak certainly had a major impact on the Indonesian economy. The financial success of businesses involved in the transport sector is undoubtedly affected by this. This study aims to compare the financial performance of business actors in the transportation sector before and during the Covid-19 pandemic. To measure financial performance, the current ratio, return on assets, and return on equity will be used in this study. This type of research uses quantitative descriptive research. The population of this study includes all transportation-related companies listed on the Indonesia Stock Exchange between 2019-2020. The sampling technique used is purposive sampling. Wilcoxon signed rank test and Paired Sample t-test were used to test the hypothesis. SPSS 25 software is used in data management in this study. The findings show that there is a significant difference in the financial performance of transportation companies in terms of liquidity and profitability ratios during a pandemic from the evaluation results of the mean difference test using the Wilcoxon signed rank test method for the variable current ratio and return on equity with the SPSS program. The profitability ratios measured using the variable return on assets also show that there is a significant difference between financial performance before and during the Covid-19 pandemic which was tested using a paired sample t-test.